Aspect-based sentiment analysis using SemEval and Amazon datasets - Hasib, Tamanna; Rahin, Saima Ahmed (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.